MEMPERBAIKI CITRA NEGATIF BIROKRASI INDONESIA - Rahmawati Rahmawati (Universitas Sultan Ageng Tirtayasa, 2010)
In public service, a very strong orientation of power during the New Order has made the bureaucracy became increasingly distant from its mission to provide public services. Bureaucracy and its officials more authority than the position itself as a public servant. Negative image of public bureaucracy today is inseparable from the history of the formation factor bureaucracy itself. In addition to that, the culture of the people of Indonesia are more patterned paternalistic make public bureaucracy as a